The role of internal auditing on effective use of financial resources in government agencies: The case study of Morogoro urban water supply and sewerage authority (MORUWASA) - James, Martha (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Accounting and Finance (Msc A & F) of Mzumbe University